Good Vibes Only: Gen Z Emerging Adult’s Perspective On Career Planning - Afina Alin Kinanti; Ni Putu Adelia Kesumaningsari; Yuan Yovita Setiawan (Green Publisher, 2025)
Gen Z refers to individuals born between 1995 and 2010, often characterized by high curiosity and growing up in a fully digital world. These traits may influence how they plan and approach their careers. This study explores how Gen Z individuals, during their emerging adulthood, perceive their current careers and plan for their future, as well as the factors they consider in this process. Therefore, this study aim is to understand, explore, or explain specific aspects of Gen Z's career planning. The study involved three female students aged 21–22 as participants. Data were analyzed using Interpretative Phenomenological Analysis (IPA), which revealed several key themes: career identity exploration, career decision inspiration, career preference, career meaning, and perceived career constraints. The findings indicates that Gen Z's unique characteristics, their immersion in the digital landscape, and personal goals significantly influence their career meaning and career planning, alongside with how they see occupation. This research provides valuable insights for families, educators, and labor market practitioners to better support Gen Z in navigating their career journeys, ultimately helping create work environments that align with Gen Z's aspirations.